2019
DOI: 10.21511/imfi.16(1).2019.01
|View full text |Cite
|
Sign up to set email alerts
|

The association between Corporate Social Responsibility Disclosure and accounting-based financial performance: a Kuwaiti evidence

Abstract: The current study aims at extending prior accounting research on the association between Corporate Social Responsibility Disclosure (CSRD) and Corporate Financial Performance (CFP) using a sample of listed firms on Kuwait Stock Exchange (KSE) from 2011 to 2012. It conducts a regression analysis to investigate the association between CSRD and CFP, as well as investigates the impact of firm size, leverage, and industry affiliation as the key determinants suggested by prior research on the level of CSRD. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Mandatory and voluntary studies on CSR has also received attention in both developing and developed economies (Mobus, 2005;Ackers and Eccles, 2015;Fatima et al, 2015;Kend, 2015;Arena et al, 2018;Karaman et al, 2018;Khan et al, 2019). Furthermore, previous studies also showed a mixed association between firm performance and CSR (Rodríguez-Ruiz et al, 2016;Al-Hajri and Al-Enezi, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mandatory and voluntary studies on CSR has also received attention in both developing and developed economies (Mobus, 2005;Ackers and Eccles, 2015;Fatima et al, 2015;Kend, 2015;Arena et al, 2018;Karaman et al, 2018;Khan et al, 2019). Furthermore, previous studies also showed a mixed association between firm performance and CSR (Rodríguez-Ruiz et al, 2016;Al-Hajri and Al-Enezi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature provides a link between CSR expenditure and financial performance and also between CSR policy and financial performance but with mixed findings (Manchiraju and Rajgopal, 2017;Shahbaz, 2018;Buallay, 2019;Choi et al, 2019). Similarly, there is a link between financial performance and CSR (Rodríguez-Ruiz et al, 2016;Al-Hajri and Al-Enezi, 2019). However, there are no studies that examined the moderating effect of mandatory CSR reporting in the association between CSR expenditure and financial performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the paper also contributes to agency theory (Jensen, 1986) by examining the principal-agent problems that may arise from holding liquid resources in the GCC. Finally, this paper extends our knowledge of how the institutional environment, particularly in emerging economies, may influence the quality of a firm's cash management practices (Al-Amri et al, 2015).…”
Section: Introductionmentioning
confidence: 67%
“…The prevalence of oil production in the GCC market enabled many firms to accumulate and allocate their liquid resources to value-generating opportunities . Further, the GCC provides an important context in terms of institutional development and governance practices (Al-Malkawi et al, 2014), which influences how decision-makers allocate the firm's slack resources in these emerging markets (Al-Amri et al, 2015;Malen and Vaaler, 2017). To examine this relationship, we first unpacked slack resources to available, recoverable and potential slack (Daniel et al, 2004;Titus et al, 2022), and then proceed to investigate their separate effects on a firm's financial performance in the GCC economies.…”
Section: Introductionmentioning
confidence: 99%